Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T20:58:33+01:00
Z km/h na m/s dzielisz przez 3.6
z m/s na km/h mnożysz przez 3.6
60km/h : 3.6 = 16.67 m/s
25km/h - 6.94 m/s
5m/s - 18 km/h
30m/s - 108 km/h
5 4 5
2009-12-15T21:07:30+01:00
Km/h= 1000m/3600s
m/s=1/1000m:1/3600s

60km/h - m/s
60*1000:3600= 60000:3600=600:36= w przybliżeniu 17 m/s

25km/h - m/s
25*1000:3600= 25000:3600=250:36= w przybliżeniu 7 m/s

5m/s -km/h
5*1/1000:1/3600=5*1/5:1/18=5*1/5*18=5*18/5=18 km/h

30m/s - km/h
30*1/1000:1/3600=30*1/5:1/18=30*1/5*18=30*18/5=6*18= 108km/h
3 3 3